The Role of Curcumin and Its Derivatives in Innate Immune Response of Macrophages - Retno Murwanti; Anami Riastri; Andayana Puspitasari Gani (Institute for Halal Industry and System (IHIS) Universitas Gadjah Mada, 2022)
Curcumin, a diarylheptanoid, is the active compound isolated from the rhizomes of Curcuma species. Curcumin can modulate mechanisms in inflammatory-related immunomodulatory. The two methoxy groups in aromatic rings in the structure of curcumin play a role in the anti-inflammatory. Macrophages are crucial cellular components of innate immunity. For this reason, this review aims to assess the role of curcumin and its derivatives in the innate immune response of macrophage cells. Curcumin as anti-inflammatory releases inflammation mediators such as cytokines, nitric oxide, reactive oxygen species, and others. Curcumin regulates innate immune via NLRP3 inflammasomes, nuclear factor-kappa B, mitogen-activated protein kinase, and Janus kinase1/2‐signal transducer and activator of transcription protein1 signaling pathway. However, curcumin has limited clinical application, especially solubility and bioavailability. Therefore, a structure and formula modification of curcumin was developed. This review also discusses no evidence of curcumin's mutagenicity, genotoxicity, and toxicity. Thus, the brief information provided in this review investigates the role of curcumin in macrophage cells.